The Latin American university at the crossroads: threats, challenges, and solutions´´ - Cuño Bonito, Justo (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2016)
This paper reviews the university as an institution, in general, in order to juxtapose the founding principle of universalism with the reductionist functionalism to which it is now limited, too constrained and dispirited to generate the fundamental critical thinking needed for the development of Latin American societies. The research is based on the hypothesis that the objective of the current neoliberalism is to subvert the universalist values which generate critical thinking in the university, so as to accommodate them to the immediate needs of large multinational corporations, where the university exists as a mere supplier of “specialized human capital”. In terms of methodology, this article reviews several bibliographical sources pursuing the proposed objectives,and contrasting the old university models with the new neoliberal paradigms. This research is supported by recent studies by specialists such as: Marvin Brown, Jean - Jacques Solomon, Mario Heler, Marta Harnecker, Francisco Lopez Segrera, Hugo Aboites, Carlos Bustos, Imanol Ordorika, Sheila Slaughter, Larry Leslie, Pablo Gentili or Franz Hinkelammert, among others. Additionally, documents form UNESCO (International Institute for Education pPnning are analyzed, like the one entitled “Trends in Higher Education in Latin America and the Caribbean” (Caracas, 2008) and “Educational situation in Latin America and the Caribbean: Towards quality education for all by 2015 “, published in 2013 by the Regional Bureau of education for Latin America and the Caribbean (Santiago de Chile, 2013).